The effects of illumination, temperature and 6-benzylaminoprine on asymbiotic seed germination and protocorm development "in vitro" in the achlorophyllous orchid Gastrodia pubilabiata Sawa - Godo, Toshinari; Hashimoto, Toshimasa; Nakata, Masashi; Miyoshi, Kazumitsu (In vitro cellular & developmental biology. Plant, 2020)
We examined the effects of culture conditions, namely, illumination, temperature and the addition of 6-benzylaminopurine (BAP) to the germination medium, on the asymbiotic germination of mature seeds of Gastrodia pubilabiata Sawa, an achlorophyllous orchid. Mature seeds were harvested from plants at two sites, one in Toyama Prefecture and one in Chiba Prefecture, Japan. We used gellan gum-solidified New Dogashima medium as the basal medium. The maximum frequency of germination of the seeds in darkness was approximately 65%. BAP had no stimulatory effect on seed germination, but accelerated protocorm development. Necessary conditions for successful germination of seeds and subsequent development of seedlings from mature seeds of Gastrodia pubilabiata clarified in this study are prerequisites not only for conservation of biodiversity but also for the elucidation of the life cycle of this achlorophyllous orchid.